2017
DOI: 10.4103/jcd.jcd_171_16
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of effect of different disposable infection control barriers on light intensity of light-curing unit and microhardness of composite - An in vitro study

Abstract: Aims:This study evaluated effect of infection control barriers on light intensity (LI) of light-curing unit (LCU) and microhardness of composite.Materials and Methods:Four different disposable barriers (n = 30) were tested against the control. LI for each barrier was measured with Lux meter. One hundred and fifty Teflon molds were equally divided into five groups of thirty each. Composite was filled in bulk in these molds and cured without and with barrier. Microhardness was evaluated on top and bottom surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
2
8
0
3
Order By: Relevance
“…Air bubbles can further increase the amount of refraction, decreasing the passage of light and the effectiveness of curing the material. This effect probably occurred in polyethylene groups as the material does not overlap with the LED tip, increasing the refraction of light (Khode et al,2017;Shortall et al, 2016;Pollington et al,2009). According to Cadenaro et al (2019) and Rueggeberg et al (2017), biological barriers can reduce irradiance of up to 40%, which would compromise polymerization of conventional composite resins (Reis & Loguercio 2007;Mendonza et al,2020).…”
Section: Discussionmentioning
confidence: 99%
“…Air bubbles can further increase the amount of refraction, decreasing the passage of light and the effectiveness of curing the material. This effect probably occurred in polyethylene groups as the material does not overlap with the LED tip, increasing the refraction of light (Khode et al,2017;Shortall et al, 2016;Pollington et al,2009). According to Cadenaro et al (2019) and Rueggeberg et al (2017), biological barriers can reduce irradiance of up to 40%, which would compromise polymerization of conventional composite resins (Reis & Loguercio 2007;Mendonza et al,2020).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study suggested a reduction in radiant emittance of approximately 10% [ 43 ]. In contrast, others suggested that there was no marked detrimental effect on polymerization [ 44 ]. Using disinfectants to clean the light tips also reduces the reflector efficiency of the tips [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…[28] A study by Khode et al . [29] tested the effect of using four different disposable barriers on the light intensity against the control group where no barrier was used and found that there was a statistically significant reduction in light intensity with all ICBs, but the hardness ratio was only significantly affecting with using Latex cut glove pieces (LCGP) as an ICB. They recommended the use of disposable ICBs except the LCGP.…”
Section: Discussionmentioning
confidence: 99%